Promelanogenic Effects by an Annurca Apple-Based Natural Formulation in Human Primary Melanocytes - Ferraro MG; Piccolo M; Pezzella A; Guerra F; Maione F; Tenore GC; Santamaria R; Irace C; Novellino E (Dove Medical Press, 2021)
Maria Grazia Ferraro,1 Marialuisa Piccolo,1 Alessandro Pezzella,2 Fabrizia Guerra,1 Francesco Maione,1 Gian Carlo Tenore,1 Rita Santamaria,1 Carlo Irace,1 Ettore Novellino1 1Department of Pharmacy, School of Medicine and Surgery, University of Naples “Federico II”, Naples, 80131, Italy; 2Department of Chemical Sciences, University of Naples “Federico II”, Naples, 80126, ItalyCorrespondence: Carlo Irace;Rita SantamariaDepartment of Pharmacy, School of Medicine and Surgery, University of Naples “Federico II”, Via D. Montesano 49, Naples, 80131, ItalyTel +39 081 678416; +39 081 678421Fax +39 081 678403Email carlo.irace@unina.it; rita.santamaria@unina.itIntroduction: Melanocytes are engaged in synthesis, transport, and release of pigments at the epidermal-melanin units in response to the finely regulated melanogenic pathway. A multifaceted combination of both intrinsic and extrinsic factors – from endocrine and paracrine dynamics to exogenous stimuli such as sunlight and xenobiotics – modulates expression and activity of proteins involved in pigmentation, including the rate-limiting enzyme tyrosinase. As well as playing critical physiological functions comprising skin photoprotection, melanins define hair and skin pigmentation which in turn have impacted considerably to human social communication since time immemorial. Additionally, numerous skin diseases based on pigmentation alterations can have serious public influence. While several melanogenesis inhibitors are already available, the number of melanin activators and tyrosinase stimulators as drug-like agents is still limited.Methods: To explore the biological effects of an Annurca Apple-based nutraceutical preparation (AMS) on melanin production, experiments in cellular models of human skin were performed. Both primary cultures and co-cultures of epidermal melanocytes (HEMa) and follicular keratinocytes (HHFK) were used.Results: We show that AMS, by now branded for its cutaneous beneficial effects, induces in total biocompatibility a significant promelanogenic effect in human primary melanocytes. In line, we found melanin cytosolic accumulation consistent with tyrosinase up-regulation.Conclusion: Disposal of skin pigmenting agents would be attractive for the treatment of hypopigmentation disorders, to postpone skin photoaging or simply for fashion, so that discovery and development of melanogenesis stimulators, especially from natural sources, is nowadays a dynamic area of research.Keywords: melanins, skin pigmentation, tyrosinase, skin pigmenting agents, natural bioactive molecules